Low morphological and genetic variation within the glass-perchlet Parambassis siamensis (Teleostei: Ambassidae) in Peninsular Malaysia - Ghazali, Siti Zafirah; Lavoué, Sébastien; Zain, Khaironizam Md.; Jamaluddin, Jamsari Amirul Firdaus; Ahmad, Amirrudin; Ratmuangkhwang, Sahat; Nor, Siti Azizah Mohd (Zootaxa, 2022)
We compare several populations of the glass-perchlet Parambassis siamensis (Fowler 1937) (Teleostei: Ambassidae) sampled throughout Peninsular Malaysia to determine their degree of differentiation, using both morphological and molecular characters. Our morphological analyses do not show evidence for the presence of more than one species, with the range of morphometric and meristic characters overlapping among populations. Our genetic analysis using partial sequences of the mitochondrial gene coding for the protein cytochrome c oxidase I (COI) reveals the existence of two clades that diverge from each other by a minimum uncorrected p-distance of 2.2%. The first clade comprises of specimens from south-eastern Peninsular Malaysia (Pahang and Endau-Rompin River basins) along with those from Cambodia (lower Mekong River). The second clade comprises of specimens from western Peninsular Malaysia (Selangor, Kurau, Perak, Muda and Kerian River basins) and north-eastern Peninsular Malaysia (Terengganu River basin), along with those from Chao Phraya River basin nearby Bangkok (type locality of P. siamensis). The presence of specimens with numerous melanophores on body sides in each of these two clades indicates that body marking pattern is not a valuable taxonomic character. This finding supports the conclusion that Chanda punctulata Fraser-Brunner 1955 is a junior synonym of P. siamensis. Altogether, our results support the hypothesis that all populations of P. siamensis in Peninsular Malaysia (along those from Chao Phraya and lower Mekong basins) are conspecific, comprising two genetically distinct, although close lineages. We further discuss the phenotypic plasticity within P. siamensis in relation to lotic and lentic habitats. Finally, we briefly discuss some implications for biogeography and possible causes explaining the distribution pattern.